2020
DOI: 10.1128/mbio.01581-20
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus ATP Synthase Promotes Biofilm Persistence by Influencing Innate Immunity

Abstract: Staphylococcus aureus is a major cause of prosthetic joint infection (PJI), which is characterized by biofilm formation. S. aureus biofilm skews the host immune response toward an anti-inflammatory profile by the increased recruitment of myeloid-derived suppressor cells (MDSCs) that attenuate macrophage proinflammatory activity, leading to chronic infection. A screen of the Nebraska Transposon Mutant Library identified several hits in the ATP synthase operon that elicited a heightened inflammatory response in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 63 publications
(94 reference statements)
0
29
0
Order By: Relevance
“…In this latter study, we searched the antibodies produced by dairy cows which were exposed to S. aureus but remained healthy, hypothesizing that the antibodies repertoire directed against these specific S. aureus proteins contributed to mastitis resistance. The first S. aureus protein, the so-called SAS protein, plays a pivotal role in dictating biofilm growth and structure [ 33 ], enhances tolerance of S. aureus towards some host antimicrobial peptides of the innate immunity [ 34 ], inhibits pro-inflammatory cytokine production by monocyte-derived macrophages and myeloid-derived suppressor cells, and renders S. aureus more resistant to the bactericidal activity of monocyte-derived macrophages [ 33 ]. The second S. aureus SDD protein is critical for bacteria survival and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In this latter study, we searched the antibodies produced by dairy cows which were exposed to S. aureus but remained healthy, hypothesizing that the antibodies repertoire directed against these specific S. aureus proteins contributed to mastitis resistance. The first S. aureus protein, the so-called SAS protein, plays a pivotal role in dictating biofilm growth and structure [ 33 ], enhances tolerance of S. aureus towards some host antimicrobial peptides of the innate immunity [ 34 ], inhibits pro-inflammatory cytokine production by monocyte-derived macrophages and myeloid-derived suppressor cells, and renders S. aureus more resistant to the bactericidal activity of monocyte-derived macrophages [ 33 ]. The second S. aureus SDD protein is critical for bacteria survival and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The most upregulated protein was the ATP synthase gamma chain (AtpG). AtpG belongs to the ATP synthase operon, the genes of which encode the subunits of the ATP synthase catalytic core, the central metabolic protein driven by the proton motive force generated by the respiratory chain [ 42 ]. With regard to S. aureus , a recent study identified that AtpG was needed for virulence in a mouse model of skin and soft tissue infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this latter study, we searched the antibodies produced by dairy cows exposed to S. aureus but remained healthy, hypothesizing that the antibodies repertoire directed against these specific S. aureus proteins contributed to mastitis resistance. The first S. aureus protein, socalled SAS protein, plays a pivotal role in dictating biofilm growth and structure [33], enhances tolerance of S. aureus towards some host antimicrobial peptides of the innate immunity [34], inhibits pro-inflammatory cytokines production by monocyte-derived macrophages and myeloid-derived suppressor cells and renders S. aureus more resistant to the bactericidal activity of monocyte-derived macrophages [33]. The second S. aureus SDD protein is critical for bacteria survival and proliferation.…”
Section: Discussionmentioning
confidence: 99%